Why do women engineers leave the engineering profession? The roles of work–family conflict, occupational commitment, and perceived organizational support - Singh, Romila; Zhang, Yejun; Wan, Min (Maggie); Fouad, Nadya A. (Human Resource Management, 2018)
This study investigated the factors that underlie the relationship between work–family conflict (WFC) and women engineers' intention to leave the occupation. The study draws from three theories: Conservation of Resources (COR) theory, turnover theory, and Rhodes and Doering's (1983) integrated model of career change. We proposed that both work interference with family (WIF) and family interference with work (FIW) influence women's intention to leave an engineering occupation by decreasing their commitment to the occupation. Using insights from the above theories and models, we further examined how perceptions of support from the organization changed the relationship between commitment to the occupation and intention to leave the occupation, as well as how conflict between work and family was related to intention to leave the occupation. We tested our predictions using time‐lagged data from a sample of 245 women engineers. The results revealed that occupational commitment mediated and explained the positive relationship between FIW and occupational turnover intentions but not the relationship between WIF and occupational turnover intentions. In addition, perceptions of organizational support influenced the relationship between occupational commitment and occupational turnover intentions and also the indirect relationship between FIW and occupational turnover intentions. Theoretical and practical implications of the findings as well as future research directions are discussed.